Environmental science projects for young scientists - Rainis, Kenneth G. (New York : F. Watts, 1994)
Focuses on projects directly related to the environment.
Includes bibliographical references and index.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Environmental sciences -- Study and teaching -- Activity programs -- Juvenile literature; Environmental sciences -- Experiments; Experiments; Environment -- Experiments; Environmental protection; Science -- Experiments